Determinants of Indonesia’s Regional Economic Growth During The Era of Regional Autonomy - Khubbi Abdillah; Alfin Maulana; Aminatuzzuhro (Jurnal Ekonomi Pembangunan, 2023)
Economic growth is one measure of the success of a region, as seen by the increasing amount of Gross Regional Domestic Product (GRDP) produced from time to time. The urgency of this study is that the determinants of regional economic growth have not included many exogenous variables in the model, especially non-economic variables. The results for estimating the economic growth model do not reflect the actual conditions of regional economic growth, so strategies for encouraging sustainable regional economic growth cannot be realized. This research aims to know and analyze the determinants of regional economic growth in 34 provinces in Indonesia. The approach used in this study is a quantitative method with static and dynamic panel data regression in the 2015-2022 timeframe. The best way to interpret this study is the two-step system GMM model. The findings of this study conclude that fiscal decentralization, capital expenditure, democracy index, happiness index, and internet access positively impact economic growth. Recommendations for this research include increasing regional self-reliance by exploring tax potential for development, providing space for freedom for the community, increasing people's living standards to make them happier, and encouraging infrastructure development so that investors are willing to invest in growing people's employment opportunities.